(untitled) (Research, Society and Development, 2022)
The entrepreneurship consists of a set of actions in order to act with innovation and generate satisfactory income. Entrepreneurship requires persistence, initiative and creativity. Thus, the present work is a narrative literature review and aims to contextualize business entrepreneurship practices within the scope of Nursing. Data collection was performed electronically using the health terminologies "entrepreneurship" and "Nursing", interrelated by the Boolean operator "AND", including complete and free articles published between 2017 and 2021, published in Portuguese and excluding duplicates. 65 articles were located in the consulted databases and 11 established as the body of analysis. The review described the justifications for the search for and adherence to entrepreneurial activities, the profile of the enterprising Nurse, the possible areas of action in business entrepreneurship for nurses and the challenges of entrepreneurial practice in Nursing, demonstrating that entrepreneurship is able to open a door for that Nursing is seen, with strength and protagonism, in all its potential by society, building better the Brazilian Nursing.